PEMANFAATAN TEKNOLOGI AUTOMATIC SPEECH RECOGNITION DALAM MENCIPTAKAN PEMBELAJARAN INKLUSIF: IMPLEMENTASI, EFEKTIFITAS DAN TANTANGAN - Hasbullah Azis; Esfandani Peni Indreswari; Rahmat Wisudawanto (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
Inclusive education is an educational system that provides learning opportunities for all individuals, regardless of physical or mental abilities. Research has shown that deaf students face several challenges in the educational process, including insufficient support in accessing education, a lack of diverse learning methods, difficulties in social adaptation, and instructional procedures not tailored to their needs. This Community Service Activity (PKM) aims to identify the learning challenges faced by deaf students at Sahid University Surakarta and to evaluate the effectiveness of using the speech-to-text feature in Zoom Meetings as an alternative tool in the teaching and learning process. By conducting interviews and learning simulations using Automatic Speech Recognition (ASR) technology with three deaf students of varying levels, this PKM activity found that ASR technology greatly assists deaf students in understanding lectures. However, the technology has limitations, such as its inability to translate intonation into appropriate punctuation, leading to dense, difficult-to-read text. As a result, a key challenge moving forward is for educators to learn how to adjust their intonation when delivering lectures to deaf students using ASR technology.